What Happened at the Mission Hill School? : The Struggle to Sustain a Small Democratic Progressive School in a Large Urban System - Meier, Deborah; Lyne, Heidi; Knoester, Matthew (Schools (Chicago, Ill.), 2023)
This article details the demise of a small multicultural and democratic school in a large urban district. After a successful 25-year run, a public school built on principles of progressive and democratic education was dismantled and destroyed. The article attempts to expose the contradictions and untruths in the story of Mission Hill School's destruction for three reasons: first, to challenge the dominant narrative promoted by the Boston Public Schools and the local media about this school; second, to honor the educators and families who believed in it and worked to create and sustain it; and finally, to make public how an urban school system can systematically destroy a school that encourages creative and critical thinking and democratic practices. This examination is important so those who care about these ideas can better advance and defend them. Although this story is not a joyful recounting, it is important to be open-eyed about both the successes and struggles of creating more inclusive and responsive democratic and progressive educational communities.